Experimental shrinkage testing on concrete masonry units and walls with different curing conditions - Parsekian, G. A.; Barbosa, K. C.; Camacho, J. S. [UNESP]; Felipe, A. S. (My University, 2016)
This paper reports on an experimental program for measuring shrinkage of concrete masonry units and walls. Tests were carried out on blocks of 4.5, 8.0 and 14.0N/mm2 strengths (with respect to gross area); different suppliers and curing procedures including air curing and moist or steam curing were investigated. The shrinkage tests on the blocks were carried out as recommended in ASTM C426 [1], using the whole block as the specimen and with gauge measuring points (discs) attached to its sides. Three variations of this configuration were also tested: a face-shell prism cut from a whole block with gauge discs attached to the sides, the same specimen with gauge discs attached to the top and bottom and whole blocks with gauge discs attached to the top and bottom. For the case of gauge discs attached to the sides, a Humboldt strain gauge was used to measure deformation. In the case of the gauge discs being attached to the top and bottom, a comparator gauge was used. Small walls, 120 to 100cm, were built inside the laboratory were gauge discs were attached at several points. The deformations between vertical and horizontal lines were measured for at least one year. Also, deformation on control blocks left inside the laboratory in front of each wall, submitted to the same environmental conditions of the wall, were also controlled. The results of the concrete block shrinkage tests were hardly influenced by the type of initial three-day cure, although different shrinkage values were observed in the control blocks for each cure type. Regarding the test procedures, only small differences in the results were obtained with whole blocks or the face shell-prisms, when readings were taken on the sides of the specimen. The use of whole blocks with gauge discs on the top and bottom was shown to be inadequate. However, it may be possible to use top and bottom gauge discs on face-shell prisms, but more investigation into this test procedure is needed to improve results. The influence of initial cure on the wall specimens was noted in that the total shrinkage was nearly equal to that measured on control blocks. The total shrinkage measured after one year is reported for each wall.
Keywords: Concrete block; Masonry; Moisture movement; Shrinkage